IMPLEMENTASI PENDIDIKAN KARAKTER SEBAGAI DHARMA AGAMA DAN DHARMA NEGARA - I Nyoman Kiriana (JIA (Jurnal Ilmu Agama), 2017)
The existence of social pathology is increasingly apprehensive at this time, should be found the best solution in handling it. One way to do is to realize the maximum character education in the life of society and state. Character education should be implemented starting from the nearest environment that is family, society and nation and state. Character education is a systematically designed and executed effort to help learners understand the values ​​of human behavior related to God Almighty, self, fellow human being, environment, and nationality embodied in thoughts, attitudes, feelings, words , and deeds based on religious norms, law, etiquette, culture, and customs. By implementing any religious teachings at the level of living with a humanist approach, then the ultimate goal in their respective religions will be realized, as well as the form of religious dharma and dharma state.